PENGARUH KEGIATAN PRAKTIK KERJA LAPANGAN TERHADAP KEMAMPUAN PESERTA DIDIK DALAM UJI KOMPETENSI KEAHLIAN TEKNIK INSTALASI TENAGA LISTRIK SMK NEGERI 1 KEDIRI - Nugraha, Aditya Taufanbayu; Hasriadi; Ashari, Mohammad Rizal; Kholis, Nur; Purdiana, Lisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of practical field work (PKL) on students' abilities in the Electrical Power Installation Engineering Skills Competency Test (UKK) at SMK Negeri 1 Kediri which has used the independent curriculum targeting class 12 which has implemented PKL in the semester 5, totaling 64 students. The research method used is a quantitative approach with survey methods. The variables in this research are PKL activities (X1) and students' understanding (X2) as the dependent variable and the relationship between PKL and UKK (Y2) as the independent variable. To analyze the data using normality tests and hypothesis testing. The results of the analysis of the normality test for independent variables using the One Sample Kolmogrov – Simirnov Test with a significance level (Sig. (2-tailed) is the relationship between PKL and UKK showing a value of p = 0.2 based on a calculation of a 5% error probability so p > 0.05 or 0.2 > 0.05. So H1 is accepted, meaning that the relationship variable between PKL and UKK is normally distributed. The results of the correlation test analysis between variables X1 and Y1 have a correlation coefficient (r) of 0.774, significance < 0.001 for variables significance <0.001 means that there is a positive correlation between PKL activities, student understanding and UKK with a strong level of relationship. The results of hypothesis testing (T test) show the significance value of variables X1, The influence on UKK's ability in this case is labeled PKL-UKK Relationship